Euphoria FM: Music for Every Emotion - Ankith A Shettty; D Pranay; Shamanth K S; Vignesh C G (Journal Electrical and Computer Experiences, 2023)
This article presents a music-based emotion system that Incorporates live emotion detection utilizing facial expressions. Music and streaming apps are gaining popularity as they are easy to access and versatile in daily activities. The proposed system provides additional functionality to traditional music, using image analysis to predict the user's mood and play music accordingly. The aim of the system is to make customers happy by providing personalized music that can reduce stress and calm the mind. Psychological research has shown that music has a therapeutic effect on many diseases, making it an important tool in solving mental health problems. However, the current music recommendations do not take into account the user's thoughts that affect their perception of music. This offering aims to fill this gap and provide a more personalized music experience by engaging in emotional exploration.